BUGIS LOCAL WISDOM IN SHORT STORIES AS ENFORCEMENT OF LITERATURE TEACHING MATERIALS IN JUNIOR HIGH SCHOOL - Juanda Juanda (Himpunan Sarjana-Kesusastraan Indonesia (HISKI), 2023)
Local wisdom is the values passed down by ancestors to the next generation from generation to generation for the preservation of culture in a place. However, the reality is that in the current era, the millennial generation is less concerned about preserving ancestral culture, especially Bugis' local wisdom. The purpose of this study was to explore the values of local wisdom of the Bugis tribe in the short stories Fajar News Paper published online in Makassar and their relevance to the enrichment of teaching materials in junior high schools. This study uses a qualitative-interpretative method. The data in this study are words, phrases, clauses, and sentences in short stories that represent local wisdom in the Bugis tribe. The data source is a short story published by Fajar News Paper in Makassar on the web ruangsastra.com. July 2020 to January 2021 period by Dul Abdul Rahman. Determination of short story text is done by purposive sampling is a technique of determining short stories with certain criteria (Sugiyono, 2008). There are two short stories chosen in this study, namely the short story “Fish in the River’s Bajoe